2021
DOI: 10.1073/pnas.2024597118
|View full text |Cite
|
Sign up to set email alerts
|

Transparent communication about negative features of COVID-19 vaccines decreases acceptance but increases trust

Abstract: During the rapid development and rolling out of vaccines against COVID-19, researchers have called for an approach of “radical transparency,” in which vaccine information is transparently disclosed to the public, even if negative information can decrease vaccine uptake. Consistent with theories about the psychology of conspiracy beliefs, these calls predict that a lack of transparency may reduce trust in health authorities and may facilitate the spread of conspiracy theories, which may limit the long-term capa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 44 publications
5
103
3
3
Order By: Relevance
“…It is important to emphasize that findings should not be taken to suggest that authorities should not transparently disclose negative information about vaccines. A recent experimental study find that while such transparency may hinder short-term vaccine acceptance, it can uphold trust in the health authorities [8] , which is the biggest predictor of overall acceptance of COVID-19 vaccines [4] , [5] . Instead, the contribution from the present analyses is that they provide the first evidence that decisions from one national health authority during a pandemic can reach and impact the populations of other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that findings should not be taken to suggest that authorities should not transparently disclose negative information about vaccines. A recent experimental study find that while such transparency may hinder short-term vaccine acceptance, it can uphold trust in the health authorities [8] , which is the biggest predictor of overall acceptance of COVID-19 vaccines [4] , [5] . Instead, the contribution from the present analyses is that they provide the first evidence that decisions from one national health authority during a pandemic can reach and impact the populations of other countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that concerns about side effects are significantly associated with vaccine skepticism also in the context of COVID-19 vaccines [2] , [6] , [9] , [1] , [8] . Accordingly, there has been raised debates over whether the decision to suspend the AstraZeneca vaccine in some countries has potential effects on levels of acceptance when it comes to COVID-19 vaccines more generally [3] .…”
mentioning
confidence: 99%
“…Research has shown that conspiracy theories are likely to channel people's feelings of resentment toward political targets and to support radical attitudes ( 38 ). Second, questioning the integrity of the pharmaceutical companies: a general feeling of missing relevant information concerning the vaccine's effectiveness ( 39 , 40 ), and concerns about unforeseen side effects and risks of this vaccine ( 2 , 5 ). A third, indirect claim of conspiracy, which is phrased in terms of unrealistic optimism, argues that the risk of this plague, as presented by the authorities, is highly exaggerated and unjustified ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…When adverse events were reported related to the 2009 H1N1 influenza pandemic vaccine, some countries did not provide timely information about the association of the events with the vaccine, causing lack of confidence in the vaccine that subsequently influenced vaccine uptake and communication ( 11 , 12 ). Thus, sustaining trust during a pandemic is critical for health authorities, both if repeated vaccinations are necessary and in preparation for future health emergencies ( 13 ).…”
Section: Introductionmentioning
confidence: 99%